2015
DOI: 10.1016/j.quaint.2014.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoecological study of Pyrenean lowland fir forests: Exploring mid–late Holocene history of Abies alba in Montbrun (Ariège, France)

Abstract: Fir (Abies alba Mill.) occupies an important place in the Pyrenean context, where the species finds its optimal conditions in this mountain zone (800e1800 m a.s.l.). In the Pyrenees, the fir woods of Volvestre (Ari ege, France) are of particular interest because of two peculiarities of its location: its northern latitude with respect to the usual location of fir in the Pyrenean axis, and its lower altitude (330e440 m a.s.l.). This has given rise to various theories, some considering the silver fir forests as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 55 publications
3
14
0
4
Order By: Relevance
“…Palaeoecological records from the Italian Peninsula suggest that Abies alba (silver fir) , a European tree species of paramount ecological and economic relevance, formed forests under significantly warmer‐than‐present conditions during the mid‐Holocene and the Eemian (Tinner et al ., ; Di Pasquale et al ., ; Cunill et al ., ). This finding contrasts with recent modelling efforts that concluded the range of A. alba may decline in Europe in response to global warming (Maiorano et al ., ; Cailleret et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Palaeoecological records from the Italian Peninsula suggest that Abies alba (silver fir) , a European tree species of paramount ecological and economic relevance, formed forests under significantly warmer‐than‐present conditions during the mid‐Holocene and the Eemian (Tinner et al ., ; Di Pasquale et al ., ; Cunill et al ., ). This finding contrasts with recent modelling efforts that concluded the range of A. alba may decline in Europe in response to global warming (Maiorano et al ., ; Cailleret et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, other techniques of high spatial precision such as soil charcoal analysis or sedimentary macroremains analysis have confirmed this chronology and provided more information about the altitudinal and local distribution. Our group has found Abies alba on the shady and sunny sides of both slopes of the Pyrenees, at Montbrun-Bocage (Cunill et al 2015) and Vall de Madriu et al (work in progress).…”
Section: The Baseline and Range Of Natural Variability Of Abies Alba mentioning
confidence: 69%
“…In the Pyrenees, environmental geohistory studies have confirmed this trend (Jalut 1988;Pèlachs et al 2009b;Galop et al 2013;Cunill et al 2015). A study by Cunill et al (2015) in fir populations at 300 m altitude on the north slope of the Pyrenees showed that, far from being anomalies or the fruits of repopulation efforts, these arboreal masses are witness to the greater importance of firs in the past in low pre-Pyrenees zones and a presence in the area for at least 5000 years. It has not always been possible to apply the concepts of resilience, baseline, and RNV to managing these forests because we still lack knowledge of their paleoecological history and distribution.…”
Section: The Baseline and Range Of Natural Variability Of Abies Alba mentioning
confidence: 90%
See 1 more Smart Citation
“…centroeuropeos, las antracomasas específicas por nivel de muestreo raramente superan los 1.000 mg kg -1 (Touflan y Talon 2008, Bal et al 2010, Cunill et al 2015, y solo en el norte de Alemania se han encontrado niveles de alrededor de 9.000 mg kg -1 por nivel (Robin et al 2013). En el caso del nivel II (antracomasa > 112.000 mg kg -1 ), es previsible que la acumulación de carbón en torno a 12-15 cm de profundidad provenga de incendios forestales relativamente recientes a la vista de las dataciones obtenidas de los carbones más superficiales analizados, que en todos los casos han ofrecido una cronología sub-actual inferior a 300 años; la eliminación en repetidas ocasiones de la cubierta arbolada y del matorral a causa del fuego habría dejado desnudas de vegetación las laderas y, en consecuencia, expuestos los delgados y rocosos suelos a la erosión hídrica de la capa fértil.…”
unclassified